Differences in Glasglow Coma Scale Scores in Ischemic Stroke Patients Receiving Neuroprotectant Therapy - Wildhan Wisnu Wardaya, Ahmad; Oktavia, Nova (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Stroke is the leading cause of disability and the second leading cause of death worldwide after heart disease. In Indonesia, stroke is the leading cause of death. This study aims to determine differences in GCS scores in ischemic stroke patients receiving neuroprotective therapy. This is an observational analytical study with a cross-sectional design. The population was 150 ischemic stroke patients recorded in inpatient medical records, with a minimum sample size of 60. Sampling used a consecutive non-probability sampling technique. Data were analyzed univariately using frequency distribution tables and bivariately using computerized Wilcoxon and Mann-Whitney statistical tests. The results of univariate analysis showed that the majority of Ischemic Stroke patients hospitalized at RSUD 45 Kuningan received Citicoline therapy (45 patients) , 34 patients were male (56.7%), 25 patients were in the Early Elderly age range (41.7%) and 25 patients had comorbidities, namely Hypertension (41.7%). The results of bivariate analysis showed that there was a significant difference in GCS scores before and after administration of neuroprotectant therapy (p value = 0.000). There was no significant difference in GCS scores at the beginning of treatment between patients who received Citicoline and Piracetam therapy (p value = 0.090). However, there was a significant difference in GCS scores at the end of treatment between patients who received Citicoline and Piracetam therapy (p value = 0.004). Neuroprotectant therapy (Citicoline and Piratecam) can improve GCS scores at the Composmentis level of consciousness (fully conscious)